Design of the communication, power management and interchangeable sensor payload system for an inspection-class robotic platform - Knox, Greig (Department of Mechanical Engineering, 2016)
With the "golden day" being the first 24 hours after an urban disaster, after which the survival rate of victims decreases dramatically, there is a requirement for a low-cost first-response robotic platform. UCT robotics is developing a platform to fulfil this requirement, with the Scarab (Figure 0-1) - a low-cost, man-packable, throwable inspection-class robotic platform with interchangeable payloads. The system was designed to create a 1:1 human-to-robot ratio which improves the efficiency of rescue operations. Once the operator has reached the inspection void, the Scarab is thrown in where the sensor stimulus from the inspection environment is communicated, via wireless communications, from the payload back to the operator station. The interchangeable payload allows the sensor configuration to be tailored to the needs of the disaster, while reducing the cost of the platform. The design of the battery and battery management system, communications and interchangeable sensor payload for this platform are described in this report.